2009
DOI: 10.1093/ageing/afp056
|View full text |Cite
|
Sign up to set email alerts
|

SGS: a structured treatment and teaching programme for older patients with diabetes mellitus--a prospective randomised controlled multi-centre trial

Abstract: Objectives: evaluation of the effectiveness of a new structured diabetes teaching and treatment programme (DTTP) with specific didactical approaches and topics for geriatric patients with diabetes mellitus.Design: a prospective randomised controlled multi-centre trial.Setting and participants: a total of 155 geriatric patients were randomly admitted to either the new DTTP SGS (n = 83) or the standard DTTP (n = 72) for insulin-treated patients with type 2 diabetes mellitus (HbA1c 8.0 ± 1.4%, age 76.2 ± 6.3 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
11

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 19 publications
0
26
0
11
Order By: Relevance
“…Study characteristics are shown in Table S1. Risk of bias for each study was assessed and determined that five studies were considered strong quality , four studies were considered moderate , and four studies were considered weak . We screened all of the papers that were included in the Chodosh review, but none were included because they did not meet our inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Study characteristics are shown in Table S1. Risk of bias for each study was assessed and determined that five studies were considered strong quality , four studies were considered moderate , and four studies were considered weak . We screened all of the papers that were included in the Chodosh review, but none were included because they did not meet our inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…For studies with ≤ 3 months [ ], the pooled treatment effect on HbA 1c was –3 mmol/mol (–0.3%; 95% CI –0.46 to –0.06). The pooled effect on HbA 1c of studies in which the intervention lasted longer than 3 months was –1 mmol/mol (–0.1%; 95% CI –0.25 to –0.04) (Fig. ) .…”
Section: Resultsmentioning
confidence: 99%
“…As interprofessional interventions specifically designed for older adults have been shown to improve glycemic control, referrals to diabetes health-care (DHC) teams should be facilitated (7)(8)(9). Payfor-performance programs improve a number of quality indicators in this age group (10,11).…”
Section: Organization Of Carementioning
confidence: 99%
“…Most of these programs, and most of the research surrounding diabetes education in the elderly, has focused on the education of diabetes self-management. [11][12][13][14][15][16][17] These types of interventions are beneficial to elderly patients aware of and living with diabetes, however, as seen in this analysis, slightly over 30% of typical community-dwelling older adults are not aware of their risk for diabetes. This data indicates that there is a large population of seniors in the community that may not be getting the appropriate screening for diabetes or gain benefit from the current model of education.…”
Section: Discussionmentioning
confidence: 73%